Antimicrobials in animal faeces (chicken, cow and swine) from the breeding farms in the upstream of Sai Gon river - Tuyet, Le Thi Bach; Nghia, Do Trong (Vietnam Journal of Science and Technology, 2022)
The widespread use of antimicrobials in husbandry has increased antimicrobial residues in animal faeces. Therefore, the investigation of antimicrobials in animal faeces is essential because they are the main cause of environmental pollution. This study analyzed and assessed samples of chiken, cow and swine faeces for seven antimicrobials, namely trimethoprim (TRI), ormethoprim (ORM), ofloxacin (OFL), norfloxacin (NOR), tetracycline (TET), chlortetracycline (CTE) and tylosin (TLS). Samples were taken from faeces heaps at breeding farms in the upstream of the Sai Gon river. The samples were analyzed in the laboratory by using high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) to determine antimicrobials. TRI, with the highest mean concentration, was found in all fecal samples (10,399 - 47,987 mg/kg) while ORM with the lowest average concentration was only detected in chicken fecal samples (542 mg/kg). CTE, with the second high mean concentration, was also found in all fecal samples (1,085 - 12,385 mg/kg), whereas TET was only detected in chicken fecal samples (9,050 mg/kg). OFL with the third average concentration, was aloso found in all fecal samples (1,516 - 9280 mg/kg), while NOR was detected in cow fecal samples at a low mean concentration (2,479 mg/kg). TLS was only found in chicken and cow fecal samples (798 - 5,802 mg/kg). These numbers show a very large amount of consumption of antimicrobials in livestock production. The results from this study are likely to encourage further monitoring of antimicrobials used in livestock production, and promote discussion of existing policies regarding the inclusion of antimicrobials in animal feed rations and veterinary medicines.